Enhancing Company Productivity through Information Sharing in Supply Chain Implementation - Ery Sugito; Elisa Kusrini (Jurnal Teknik Industri, 2023)
The lack of accuracy and slow information flow within the supply chain poses significant challenges to the sustainability of the manufacturing process. Effective information management is essential for enhancing supply chain competitiveness, encompassing increased product yield, improved product quality, cost reduction, and enhanced productivity for quicker product distribution. This research investigates the impact of information sharing on supply chain management to bolster company productivity. Additionally, it delves into the detrimental consequences of insufficient information sharing and offers solutions to ensure efficient information exchange within the organization. To achieve these research objectives, we employ a quantitative approach utilizing the Structural Equation Model (SEM)-Amos and six questionnaire variables: information sharing, information quality, information technology, supply chain management implementation, productivity, and customer satisfaction. Our findings underscore the adverse effects of limited information sharing on supply chain management performance, leading to reduced productivity. The enhancement of supply chain management hinges on effective and transparent information sharing, facilitated by disseminating clear and sustainable information throughout the company. Furthermore, ensuring employees understand supply chain management practices comprehensively is crucial. These measures are poised to contribute to increased productivity and the achievement of customer satisfaction goals.